Wage Premium of the Public Sector in Indonesia - Rizky Fitria (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2018)
Are Indonesian government officials overpaid? If they are, should Indonesia’s decision makers reduce the civil servants’ wage rate? Practically, the best comparison for the public sector’s wage is the private sector’s remuneration. Therefore, this study investigates the wage differential between public and private sectors in Indonesia. To obtain robust estimations, it needs to eliminate the effects from differences in workers’ and jobs’ characteristic as well as the selection bias problem. Therefore, it applies various methodologies such as Heckman Correction Method and Quantile Wage Regression by using the newest data retrieved from Indonesia Family Life Survey (IFLS) 5 in 2014. The results suggest that differences in wages among two sectors are positive, meaning that Indonesia’s government workers earned higher wages with respect to their private counterparts. Some of those results were consistent with former studies in other countries but revealed different trends compared to previous Indonesian data. The wage gap found in this study was higher for individuals with tertiary education level and varied along the wage distribution.